2009
DOI: 10.1038/ni.1707
|View full text |Cite
|
Sign up to set email alerts
|

Blood-derived inflammatory dendritic cells in lymph nodes stimulate acute T helper type 1 immune responses

Abstract: TH1-polarized immune responses, which confer protection against intracellular pathogens, are thought to be initiated by dendritic cells (DCs) that enter lymph nodes from peripheral tissues. We found following viral infection or immunization, inflammatory monocytes were recruited into lymph nodes directly from the blood to become CD11c+CD11bhiGr-1+ inflammatory DCs, which produced abundant interleukin 12(p70) and potently stimulated TH1 responses. This monocyte extravasation required CCR2 but not CCL2 or CCR7. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
283
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(316 citation statements)
references
References 44 publications
27
283
2
4
Order By: Relevance
“…In addition, Tip-DCs upregulated the chemokine receptors CCR1, CX3CR1 and continued to express CCR2 and CCR5, suggesting a role in inflamed tissues where they may exert a pro-inflammatory role through the production of TNF-a and NO. Although Tip-DCs do not express high levels of CCR7, we cannot exclude the possibility of their presence in lymph nodes where they prime T cells, as monocytes can migrate directly into lymph nodes via CCR2 and differentiate into DCs [28].In particular, we show that IFN-g in our CD8-DC cytokine milieu was an important factor for monocyte differentiation into cells with Tip-DC characteristics. Interestingly, the inability of monocytes to express more TNF-a and iNOS after differentiation with a certain level of IFN-g suggests that a saturating effect occurs, thereby explaining why monocytes cultured with Supernatant CD8DC or Supernatant CD8DCLPS could both differentiate into Tip-DCs despite the latter having higher amounts of IFN-g and other cytokines.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, Tip-DCs upregulated the chemokine receptors CCR1, CX3CR1 and continued to express CCR2 and CCR5, suggesting a role in inflamed tissues where they may exert a pro-inflammatory role through the production of TNF-a and NO. Although Tip-DCs do not express high levels of CCR7, we cannot exclude the possibility of their presence in lymph nodes where they prime T cells, as monocytes can migrate directly into lymph nodes via CCR2 and differentiate into DCs [28].In particular, we show that IFN-g in our CD8-DC cytokine milieu was an important factor for monocyte differentiation into cells with Tip-DC characteristics. Interestingly, the inability of monocytes to express more TNF-a and iNOS after differentiation with a certain level of IFN-g suggests that a saturating effect occurs, thereby explaining why monocytes cultured with Supernatant CD8DC or Supernatant CD8DCLPS could both differentiate into Tip-DCs despite the latter having higher amounts of IFN-g and other cytokines.…”
mentioning
confidence: 67%
“…In addition, Tip-DCs upregulated the chemokine receptors CCR1, CX3CR1 and continued to express CCR2 and CCR5, suggesting a role in inflamed tissues where they may exert a pro-inflammatory role through the production of TNF-a and NO. Although Tip-DCs do not express high levels of CCR7, we cannot exclude the possibility of their presence in lymph nodes where they prime T cells, as monocytes can migrate directly into lymph nodes via CCR2 and differentiate into DCs [28].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that mice lacking CCL19/21 (paucity of lymph node T cells or plt) display delayed but enhanced immune responses (7,33,34). Whereas there is an altered pro-Th1-type inflammatory infiltrate in immunized plt LNs (34), other studies suggest that T-cell responses in these mice may be generated in the splenic red pulp or the cortex of the LN (7), potentially contributing to the enhanced responses observed. We have demonstrated here that FAP + FRCs are critical to the initiation of T-and B-cell responses, as their depletion severely limits the pool of naïve cells in which are found antigen-specific cells.…”
Section: Discussionmentioning
confidence: 91%
“…[6][7][8], levures ou parasites [9,10]. C'est également le cas dans des modèles d'inflammation expérimentale en l'absence de pathogène [11][12][13][14][15] ou encore dans des modèles de maladies inflammatoires (asthme, colite, arthrite rhumatoïde, sclérose en plaques) [6,[16][17][18] (Figure 1). Différents groupes ont ainsi montré que, lors d'une inflammation, des monocytes injectés à des souris se différenciaient en cellules dendritiques inflammatoires [4,6,9,12,19].…”
Section: Définition Des Cellules Dendritiques Inflammatoiresunclassified
“…Différents groupes ont ainsi montré que, lors d'une inflammation, des monocytes injectés à des souris se différenciaient en cellules dendritiques inflammatoires [4,6,9,12,19]. L'utilisation de souris déficientes pour le récepteur de chimiokine CCR2, récepteur indispensable à la migration des monocytes, a permis d'aboutir à la même conclusion : l'absence de recrutement des monocytes sur le lieu d'inflammation compromet l'apparition des cellules dendritiques inflammatoires dont le nombre est alors sévèrement diminué [5,8,9,13,20]. Si l'on sait que la formation des cellules dendritiques inflammatoires n'est pas affectée par l'absence du ligand de Flt3 [19], on connaît mal en revanche les molécules impliquées dans la différenciation des monocytes en cellules dendritiques inflammatoires.…”
Section: Définition Des Cellules Dendritiques Inflammatoiresunclassified